Echocardiographic differences between the mild form of subclinical hypothyroidism and healthy subjects - Velkoska Nakova, Valentina; Krstevska, Brankica; Srbinovska Kostovska, Elizabeta; Georgievska Ismail, Ljubica; Volkanovska Ilijevska, Cvetanka; Milenkovikj, Tatjana (Bioscientifica, 2024)
Background: Treatment of subclinical hypothyroidism (ScH) when TSH is between the upper reference value and 7mU/L, especially in patients younger than 65 years is controversial. Objectives: To compare the risk factors for atherosclerosis and echocardiographic parameters in patients with ScH1 (4, 2≤TSH≤7mU/L) to euthyroid subjects and patients with ScH2 (TSH>7mU/L). Material and Methods: Prospectively 54 consecutive patients with newly diagnosed ScH (19 with TSH≤7mU/L (ScH1) and 35 with TSH>7mU/L (ScH2)) started for the first time with levothyroxine therapy, and 30 healthy subjects were recruited from the outpatient department of the University Clinic of Endocrinology in Skopje, R. of N. Macedonia. Laboratory analyses and an echocardiography study were done at the first visit and after 5 months in a euthyroid stage in patients with ScH. Results: The mean age and TSH value in ScH group were 43.1±12.4y., and 8.71± 1, 9mU/L. Compared to healthy controls, patients with ScH1 had a higher mean triglycerides and non-HDL-C ratio (1.52±0.9 vs 1.1±0.6, and 4.3±1.1 vs 3.79±0.9, P<0.05), lower E/A ratio (1.05 ± 0.25 vs 1.26 ± 0.36, P<0.05), higher E/e’ sep. ratio (8.56 ± 2.63 vs 6.04 ± 1.64, P< 0.01), higher myocardial performance index (MPI) (0.47 ± 0.09 vs 0.43 ± 0.07, P< 0.05), lower global longitudinal strain (GLS) (-19.34 ± 2.0 vs -20.9 ± 1.7%, P< 0.05), and lower S wave derived by tissue Doppler imaging (0.074 ± 0.01 vs 0.092 ± 0.01 m/s, P< 0.01). Compared to ScH2, patients with ScH1 have lower GLS but without statistical significance. Levothyroxine treatment (L-T4T) in patients with ScH1 contributed to higher EF (61.9 ± 5.2 vs 63.1 ± 4.6%, P< 0.05), lower E/e’ sep. ratio (8.56 ± 2.63 vs 7.21 ± 2.23, P< 0.05), and lower MPI (0.47 ± 0.09 vs 0.43 ± 0.05%, P< 0.05), compared to values in ScH1 patients at baseline. The same parameters were improved in the ScH2 group after L-T4T. Conclusions: In a small study, patients with ScH1 vs healthy individuals had subtle changes in certain parameters that indicate involvement of diastolic function of the left ventricle in ScH, and these parameters improved after L-T4T.
Keywords: diastolic function; subclinical hypothyroidism